Professional Performance: Analysis Based on the Optimization of Infrastructure and Work Ethics of Arts and Culture Teachers - Daeng Ayub Natuna; Yessica Julianti; Muhammad Jais; Wilson Wilson; Ria Rizkia Alvi (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to determine and analyze the influence of infrastructure optimization on the professional performance of Cultural Arts Teachers at Pekanbaru City High School; find and analyze the effect of work ethic on the professional performance of the Arts and Culture teachers at Pekanbaru City High School; found and analyzed the influence between the optimization of infrastructure and work ethic on the professional performance of the Arts and Culture teacher at Senior High School in Pekanbaru. The research methodology used in this study is a quantitative research method. The research tool used in data collection is a questionnaire. The population in this study were all 87 teachers of Cultural Arts at Pekanbaru City High School, with a sample of 47 teachers in this study. Methods of data analysis in this study using descriptive statistical analysis methods and inferential statistical analysis methods. Managing analytical, statistical data in the description of this study using Microsoft Excel tools and the Windows 23 version of SPSS. The results shown in the study are for the following reasons; a significant and positive effect was obtained between the variables of infrastructure optimization on the Professional Performance of Cultural Arts Teachers at Pekanbaru City Senior High School; a significant and positive effect was obtained between work ethic on the Professional Performance of Cultural Arts Teachers at Pekanbaru City Senior High School; There is a significant and positive influence between the optimization of infrastructure and work ethic variables on the Professional Performance of Cultural Arts Teachers at Pekanbaru City Senior High School. This means that the better or proper the facilities and infrastructure at the school, the higher the teacher's professional performance, then the higher the teacher's work ethic towards his work, the higher the teacher's professional performance, as well simultaneously.